UPAYA KEPOLISIAN DALAM MEWUJUDKAN SISTEM PERADILAN PIDANA TERPADU PADA PROSES PENYIDIKAN TINDAK PIDANA NARKOTIKA: Studi Pada Ditresnarkoba Polda Sumbar - Muhammad Hendri Zulfi (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
The integration of the judicial sub-system in the stage of investigating narcotics crime carried out by the Directorate of Narcotics of the West Sumatra Regional Police in the implementation of various obstacles was still encountered. The West Sumatra Police Directorate of Drugs Efforts in Realizing an Integrated Criminal Justice System During the Narcotics Crime Investigation Stage is to coordinate with BNN on rehabilitation recommendations. After the investigation is deemed completed, the investigator submits the case file to the public prosecutor and takes the pre-prosecution stage. Relationship with the District Court with its decision to give permission for forced efforts by investigators. The success of the integrated criminal justice system is highly dependent on the cooperation and coordination of all components involved in the system. Fragmentary symptoms still appear to be in the operational motion of the criminal justice sub-system, especially at the investigation stage. Another obstacle is that the investigation institution is not yet independent. The coordination system that will be carried out with the public prosecutors is also not done well. Unification of the understanding of the results of the investigation is a matter that determines the results of the investigation.